PENERAPAN TEKNOLOGI SPINNER UNTUK MENINGKATKAN PRODUKSI MINUMAN BUBUK JAHE INSTAN DI UKM AR-RIDWAN KOTA PADANG - Sri mutiar; Ruri Wijayanti; Dewi Arziyah; Lisa Yusmita; Malse Anggia; Ariyetti Ariyetti (LPPM Universitas Andalas, 2023)
Instant spice drinks that function to maintain body stability and are believed to be able to increase the body's immunity are developing very rapidly in the era of the Covid-19 pandemic. Ginger is a spice with various benefits, providing opportunities for the Small Business industry. One of them is the instant spice drink industry player